2016
DOI: 10.3892/mmr.2016.5147
|View full text |Cite
|
Sign up to set email alerts
|

Role of peroxiredoxin 2 in H2O2-induced oxidative stress of primary Leydig cells

Abstract: Late‑onset hypogonadism is defined as a condition caused by a decline in the levels of testosterone with aging. One of the major factors contributing to the low levels of testosterone is the accumulation of reactive oxygen species (ROS) in Leydig cells during the ageing process. Peroxiredoxin 2 (Prdx2), a member of the peroxiredoxin family, is an antioxidant protein, the predominant function of which is to neutralize ROS. However, its role in Leydig cells remains to be elucidated. In the present study, primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 24 publications
1
10
0
1
Order By: Relevance
“…Sirt2, 3 and 5 decreases the cellular levels of ROS or promotes the transcription of manganese superoxide dismutase (MnSOD) (Wang et al, 2007 ; Lin et al, 2013 ; Pillai et al, 2016 ; Yang et al, 2016 ). Pink1 overexpression could suppress ROS formation, and Prdx2 is an antioxidant protein, whose predominant function is to neutralize ROS (Wang et al, 2011 ; Chien et al, 2013 ; Avitabile et al, 2014 ; Duan et al, 2016 ). Therefore, down-regulation of above identified genes (cataloged into class 2) during denervation-induced skeletal muscle atrophy might be due to their function as a negative regulator of ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…Sirt2, 3 and 5 decreases the cellular levels of ROS or promotes the transcription of manganese superoxide dismutase (MnSOD) (Wang et al, 2007 ; Lin et al, 2013 ; Pillai et al, 2016 ; Yang et al, 2016 ). Pink1 overexpression could suppress ROS formation, and Prdx2 is an antioxidant protein, whose predominant function is to neutralize ROS (Wang et al, 2011 ; Chien et al, 2013 ; Avitabile et al, 2014 ; Duan et al, 2016 ). Therefore, down-regulation of above identified genes (cataloged into class 2) during denervation-induced skeletal muscle atrophy might be due to their function as a negative regulator of ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA extraction and qPCR were carried out as described previously (Duan et al 2016). The primer sequences (synthesized by Shanghai Generay Biotech Co., Ltd., Shanghai, China) were as follows: sense 3ʹgaaactgctgcctcacatccg-5ʹ and anti-sense 3ʹ-gctggcacagtgacctcacacg-5ʹ for acidic ribosomal phosphoprotein P0 (36B4); sense 3ʹ-cagcagcccatgaattaccc-5ʹand anti-sense 3ʹ-caccggtagccacagatttg-5ʹ for FasL; and sense 3ʹ-agacatgctgtggatctggg-5ʹ and anti-sense 3ʹ-ttgacagcaaaatgggcctc-5ʹ for Fas.…”
Section: Rna Extraction and Quantitative Real-time Pcrmentioning
confidence: 99%
“…Western blot analysis was performed as described previously (Duan et al 2016). Briefly, following treatment, cells in a 6 cm cell culture dish were then washed twice with ice-cold PBS and lysed in 150 µl of ice-cold radioimmunoprecipitation assay buffer (RIPA, Sigma, America) for 10 min on the ice.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Previous studies have shown that one of the known mechanisms of carcinogenesis is the activation of various signaling pathways and changes of transcription factors caused by prolonged oxidative stress [12,13]. As a key member of PRDXs family, peroxiredoxin 2 (PRDX2) has been reported to scavenge peroxides and reactive oxygen species (ROS) in cells to regulate redox status, thus participating in a variety of cellular biological functions [14][15][16]. Recent studies identify aberrant expression of PRDX2 in several types of cancers and demonstrate that PRDX2 exerts an important role in cell proliferation, death, and drug sensitivity of cancer [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%